A REVISION OF BEGONIA SECT. SYMBEGONIA ON NEW GUINEA. (31st January 2018) - Gagul, J. N.; Sands, M. J. S.; Gideon, O.; Hughes, M.
Abstract : A revision of Begonia sect. Symbegonia, endemic to New Guinea, is presented, with descriptions of five new species ( B. arauensis M.Hughes, B. asaroensis J.Gagul, B. erodiifolia Sands, B. mimikaensis Sands and B. vinkii Sands). There are 18 species now recognised, and a key is provided for their identification. Ten of the species are assessed to belong to the IUCN category Data Deficient, and eight to Least Concern.